Relating Use of Effective Responsive, Structure, and Non-Directive Control Vegetable Parenting Practices to Subscales from the Model of Goal Directed Behavior - Diep, Cassandra S.; Beltran, Alicia; Chen, Tzu- An; Thompson, Debbe; Connor, Teresia O; Hughes, Sheryl; Baranowski, Janice; Baranowski, Tom (International Journal of Child Health and Nutrition, 2016)
Parents may positively influence children’s vegetable consumption through effective vegetable parenting practices (VPP). Research has demonstrated three dimensions of effective VPP: Effective Responsiveness, Structure, and Non-Directive Control, but there is limited research investigating each separately. This study presents the modeling of Effective Responsive, Structure, and Non-Directive Control VPP using constructs from the Model of Goal Directed Vegetable Parenting Practices (MGDVPP). Parents (n=307) completed a survey on demographics, MGDVPP constructs, and effective VPP. Block regression modeling tested three models: one for each dimension of effective VPP as the dependent variable. Independent variables included validated subscales representing MGDVPP constructs: Intention, Desire, Perceived Barriers, Autonomy, Relatedness, Self-Efficacy, Habit, Anticipated Emotions, Perceived Behavioral Control, Attitudes, and Norms. Participants were racially diverse, and a majority was female, of higher socioeconomic status, and with a male child. Effective Responsive VPP was positively related to a Habit subscale. Effective Structure VPP was positively related to a Barrier, two Habit, and an Attitude subscales. Effective Non-Directive Control VPP was positively related to being a high school or GED graduate, having younger children, a Habit, and two Intentions subscales, and negatively related to an Intentions and a Perceived Behavioral Control subscales. The adjusted R2 for the Effective Responsive, Structure, and Non-Directive Control VPP models were 0.432, 0.310, and 0.515, respectively. This was the first study to relate constructs from a theoretical model to effective VPP dimensions. Research is needed to longitudinally assess the MGDVPP and test its utility in vegetable-related interventions.